1981
DOI: 10.2136/sssaj1981.03615995004500060007x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Field‐Measured Infiltration Rate

Abstract: Spatial variability of 1,280 field‐measured infiltration rates on Yolo loam (fine‐silty, mixed, nonacid, thermic Typic Xerorthents) was studied using geostatistical concepts. The measurements were made at the nodes of an irregular grid consisting of 160 rows and eight columns. Sample spacing within columns was 1 m. Columns were spaced irregularly at 1, 5, 15, and 19 m.A variogram for the 1,280 measurements was used to krige 800 additional values within five more columns and to draw a contour map of the area.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
59

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(158 citation statements)
references
References 0 publications
2
97
0
59
Order By: Relevance
“…According to Martinho (2000), owing to the soil physical changes implied to the soil surface layer in the no tillage system, it is necessary to study the spatial variabil-ity in order to adequately characterize the environment. The spatial variability can be analyzed using geostatistics that involves a sequence of procedures for the construction of contour maps (Campbell, 1978;Burgess & Webster, 1980;Vieira et al, 1981;Vauclin et al, 1983;Vauchaud et al, 1985;Wendroth et al, 1997;Vieira, 2000;Grego & Vieira, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Martinho (2000), owing to the soil physical changes implied to the soil surface layer in the no tillage system, it is necessary to study the spatial variabil-ity in order to adequately characterize the environment. The spatial variability can be analyzed using geostatistics that involves a sequence of procedures for the construction of contour maps (Campbell, 1978;Burgess & Webster, 1980;Vieira et al, 1981;Vauclin et al, 1983;Vauchaud et al, 1985;Wendroth et al, 1997;Vieira, 2000;Grego & Vieira, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of soil as an inhomogeneous media was established already at the turn of the century [Vieira et al, 1981]. Despite this, only a limited number of studies focusing specifically on the spatially variable nature of soil were published until approximately 2• decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, Wagenet (1981) and Vieira et al (1981) found a zone of influence for individual infiltration measures of 5.3 m and 50 m, respectively, on agricultural soils. Since cover (live and litter) explained only 18-36% of the variance associated with measured infiltration rates, the complex nature of rangeland soils and trampling patterns of cattle (on the grazed pasture) must account for the differences.…”
Section: Resultsmentioning
confidence: 98%
“…Most spatial variability studies of infiltration rates have been conducted on agricultural soils (Sisson & Wierenga, 1981;Vieira et al, 1981;Wagenet, 1981). A recent study (Achouri & Gifford, 1984) looked at spatial and temporal variability of infiltration rates on a seeded rangeland site in Utah.…”
Section: Introductionmentioning
confidence: 99%